Volatile organic compounds in exhaled human breath for the diagnosis of malignant pleural mesothelioma: a meta-analysis - Tingting Zhao; Tingting Zhao; Xiao Hu; Minghua Peng; Wei Wei; Ninghua Fu; Chen Chen; Zhenguang Chen; Zhenguang Chen; Zhenguang Chen (Frontiers in Oncology)
ObjectiveMalignant pleural mesothelioma (MPM) is a relatively rare thoracic tumor with a high mortality rate, making early diagnosis and treatment challenging. The present study evaluated the utility of exhaled volatile organic compounds (VOCs) in diagnosing MPM.MethodsThe Cochrane Library, PubMed, EMBASE, and Web of Science were systematically searched for clinical trials assessing the diagnostic ability of VOCs for MPM through August 30, 2024. Quality was evaluated using the QUADAS-2 tool. A meta-analysis was performed with a bivariate model for sensitivity and specificity using Stata MP 17.0 software.ResultsEight trials with 859 subjects were included. VOCs were found to have a pooled sensitivity of 0.86 (95% confidence interval [CI] 0.75–0.93), a pooled specificity of 0.73 (95% CI 0.58–0.84), and an area under the curve (AUC) of 0.88 (95% CI 0.85–0.90) in differentiating MPM patients from healthy controls. In addition VOCs had a pooled sensitivity of 0.89 (95% CI 0.83–0.93), a pooled specificity of 0.79 (95% CI 0.57–0.91), and an AUC of 0.91 (95% CI 0.88–0.93) in differentiating MPM patients from asymptomatic individuals formerly exposed to asbestos (AEx).ConclusionsAlthough the utility of VOCs in diagnosing MPM varied among clinical trials, VOCs in exhaled human breath may have a potential role in the diagnosis of MPM. Large-scale randomized clinical trials are warranted.